Perawatan Preventif Mesin Pompa Air - Trisna Mesra; Insannul Kamil; Rika Ampuh Hadiguna (Universitas Medan Area, 2023)
The Planned maintenance activities can make the production process run smoothly. The object of the research was pump machine with three phase. Based on obsevations, pumps often experience damage to critical components. This study aims to implement preventive maintenance on pump. The advantage of using preventive maintenance can determine the optimal type of maintence and maintenance time intervals for each critical component. The research stages include determining the probability density function (pdf) and reliability, determining the maintenance interval for critical component using the downtime minimization criteria that will be used to schedule maintenance and determining the cost of corrective and preventive for each critical component. The result of the application of preventive maintenance, there were three component that experienced a decrease in maintenance costs, namely the electromotor component experiencing a 23,7% cost reduction with a 52% reliability level, the radial bearing component experiencing a cost reduction by 24% with a reliability level of 66,64% and the impeller component experiencing a decrease 19,5% cost with a 69% reliability rate. While the maintenance time interval for the electromotor component is 142,4 hours, the radial bearing component is 153,5 hours and the impeller component is 168,8 hours.